Socialization of Early Savings Movement to Improve Skills in Financial Management at the Berkat Iman Orphanage - Agus Tina; Khana Saputri; Ninta Katharina; Afriza Amir; William (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
This activity is aimed at the community, especially the main focus is children who need guidance on early savings awareness. The community service team from Universitas Prima Indonesia will conduct socialization activities for children at the Berkat Iman Orphanage. The method in implementing community service is in the form of socialization and discussion between UNPRI lecturers, administrators and children of the Berkat Iman Sejahtera Orphanage. This community service activity was carried out at the Berkat Iman Sejahtera Orphanage, Jalan Sampul No. 49, Sei Putih Barat, Medan Petisah District, Medan City. The target of this community service activity is administrators and early childhood children. A total of 25 orphanage children aged 7 months - 14 years accompanied by 5 administrators have participated in the socialization activity. The results of this activity can be concluded that many children at the Berkat Iman Sejahtera Orphanage still do not know about how to save properly. Administrators at the Berkat Iman Sejahtera Orphanage have additional knowledge and understanding related to how to manage finances through saving from an early age. Administrators and children become aware of good ways to save.